Concepts of the consumer in competition, regulatory, and consumer protection policies - Decker, C (Oxford University Press, 2017)

(untitled)
Competition and economic regulation policies have traditionally been based on the conception of a “standard” consumer who is perfectly rational, has a high level of computational skills, and is invariant to the environment in which choices are made. An ever-expanding body of research concludes that, for a variety of reasons, consumers often behave in various “non-standard” ways. In light of this research, some economic regulators and competition authorities are replacing the concept of the standard consumer with the concept of the non-standard consumer. This is justified on the basis that it is more realistic and offers the potential for more effective policies anchored in the behavior of actual consumers. While there are persuasive arguments for adopting a concept of the non-standard consumer, effectively integrating non-standard consumers into relevant policies raises conceptual challenges and risks, some of which have been borne out in practice. In particular, attention needs to be given to: the specific nature of the non-standard consumer behavior; the relative proportion of consumers characterized by non-standard behavior; possible supplier responses to remedial measures; and critically, the potential unintended effects of such policies. If these parameters and challenges are acknowledged and effectively incorporated into analytical frameworks, the potential exists for better-targeted competition and regulatory policies.